Recent Advances in the Management of Feline Sporotrichosis - Stefaniszen, Amanda Garcia [UNESP]; de Oliveira Ferreira, Lucas Vinícius [UNESP]; Chalfun Guimarães-Okamoto, Priscylla Tatiana [UNESP]; Melchert, Alessandra [UNESP] (My University, 2023)
Sporotrichosis is a subcutaneous mycosis caused by species of the genus Sporothrix that has stood out in recent years, mainly in Brazil. Its importance for public health as an emerging disease is mainly associated with zoonotic transmission by domestic cats, which have a high fungal load on skin lesions, facilitating the dissemination of the agent. Classical transmission is caused by traumatic inoculation of the fungus in a con-taminated environment. Propagation between animals occurs due to close contact between cats with other cats or dogs and for humans associated with bites, scratches, and interaction with exudate from infected lesions. The clinical manifestations in felines are variable and can present as localized or fixed, disseminated, cutane-ous-lymphatic, and systemic. In human patients, mainly immunosuppressed, extracutaneous forms can occur, evolving even to fatal cases. Early diagnosis is essential to ensure that preventive measures are employed for owners, with the isolation of the etiological agent in culture being considered the gold standard. The lack of strategic plans, adequate control measures, failure to recognize and neglect the disease increases the incidence of cases, especially in more precarious population groups. Thus, due to its importance in public and animal health, the objective of this review was to highlight recent advances concerning the feline disease.
Keywords: Cat; Fungus; Public health; Sporothrix spp; Zoonosis